I14 Development of drugs against SPT4/SPT5 for the treatment of Huntington's disease. (12th September 2022) - Bahat, Anat; Dikstein, Rivka
Abstract : Spt5 is a conserved and essential transcription elongation factor that plays important roles in the transcription of inflammation and stress-induced genes. In eukaryotes Spt5 forms a complex with Spt4 transcription factor. Previously, Spt4/Spt5 has been shown to facilitate transcription of genes with lengthy stretches of multiple repeats that are hallmarks of several inherited degenerative neurological disorders including Huntington's disease (HD), ALS/FTD and SCA36. The requirement of Spt4/Spt5 for selective transcription of 3 distinct expanded repeat genes suggests for a common mechanism which is presently unknown. Nevertheless, these findings place Spt4/Spt5 as an attractive target for drugs against these diseases and potentially other nucleotide repeat expansion diseases. To search for inhibitors targeting Spt5 activity we developed a powerful and sensitive high-throughput drug screening protocol that is based on protein-protein interaction assay. This led to the identification of the first Spt5 inhibitors called SPIs that precisely mimic the effect of Spt5 depletion on basal and activated pro-inflammatory genes. Similar to Spt4/Spt5 knockdown, several SPIs also display a selective inhibitory effect on mutant (Q111/Q111) but not the WT (Q7/Q7) Htt gene. Of them, 5 drugs selectively inhibit mutant Htt gene without affecting the other Spt4/Spt5 activities, suggesting that the various activities of Spt5 can be uncoupled. Using SAR-by-catalog and chemical synthesis we identified 4 potent analogs that can inhibit Htt mutant gene in the low µM and nM range. To further develop these compounds as a potential treatment against HD we started to test the potent SPIs against HD using animal models.